PENGARUH CORONA VIRUS DISEASE (COVID-19) TERHADAP TINGKAT PERCERAIAN (STUDI DI PENGADILAN AGAMA WONOSARI) - A Tajus Subky; Izzy Al Kautsar (Universitas Muhammadiyah Mataram, 2021)
Divorce is a breaking of the marriage bond between a husband and wife before the court because of a broken family relationship disharmony on the basis of an internal or external factor that occurs. The focus of this research is how the divorce law and divorce factors during the Covid-19 period. How was the legal policy during the covid-19 period and how was the effect of covid-19 on the divorce rate in the Wonosari Religious Court. The results of this study are that the divorce rate has increased during Covid-19 in the Wonosari area because the government has implemented a new normal which has resulted in a surge in divorce cases going to court, the factors that affect the increase in divorce are the economy, the number of husbands who are laid off so that can not provide a living to his wife, 24 hours at home so the couple feels bored and conflicts arise so that the wife filed a divorce suit at court.